Broadly Protective Strategies Against Influenza Viruses: Universal Vaccines and Therapeutics - Vogel, Olivia A.; Manicassamy, Balaji (Frontiers in Microbiology, 2020)
Influenza virus is a respiratory pathogen that can cause disease in humans, with symptoms ranging from mild to life-threatening. The vast majority of influenza virus infections in humans are observed during seasonal epidemics and occasional pandemics. Given the substantial public health burden associated with influenza virus infection, yearly vaccination is recommended for protection against seasonal influenza viruses. Despite vigilant surveillance for new variants and careful selection of seasonal vaccine strains, the efficacy of seasonal vaccines can vary widely from year to year. This often results in lowered protection within the population, regardless of vaccination status. In order to broaden the protection afforded by seasonal influenza vaccines, the National Institute of Allergy and Infectious Diseases (NIAID) has deemed the development of a universal influenza virus vaccine to be a priority in influenza virus vaccine research. This universal vaccine would provide protection against all influenza virus strains, eliminating the need for the yearly reformulations of seasonal influenza vaccines. In addition to universal influenza vaccine efforts, substantial progress has been made in developing novel influenza virus therapeutics that utilize broadly neutralizing antibodies to provide protection against influenza virus infection as well as to mitigate disease outcomes during infection. In this review, we discuss various approaches toward the goal of improving influenza virus vaccine efficacy through a universal influenza virus vaccine. We also address the novel methods of discovery and utilization of broadly neutralizing antibodies to improve influenza disease outcomes.